Answer:
(A) 2k/s² M+k (B) C = -M/k
Step-by-step explanation:
Solution
Given that:
(A) Write the linearized equations of motion of the system determine the transfer function. G(s) = X(s)/Z(s).
Now
G(s) = X(s)/Z(s)
F(t) = M. d² X(t)/dt² + K X(t)......(1)
We convert the equation in the s domain
F(s) = s² M X(s) +kX (s)
F(s) =X(s) [M s² + k]
F = mgl
F(s) =X(s) [M s² + k]
mgl = X(s) [s² M +k]
F(t) = KZ(t) -----(2)
Thus
mgl/2 = kZ(s)
Z(s) = mgl/2k
So
X(s)/Z(s) = mgl/[s² m+k]/mgl/2k
Mgl/[s² M+k] *2k/mgl
Now
X (s)/Z(s) = 2k/s² M+k
(B) The next step is to determine the motion x(t) of the mass m as a function of the system parameters.
Now,
Let assume that input z(t) is a unit step
Thus
X(s) =1/s 2k/s² M+k
=1/s 2k/M[s² + k}
So,
I/s = 2k/M [ s +k/MJ] [s- k/M J]
By applying practical fractions we have the following :
A/s + B/ [s +k/MJ] +C/ [s- k/M J]
Thus,
S = 0
A (k/MJ + s) (J -k/M + J) = 2k/M
A ( 0 +k/MJ) ( 0 -k/MJ) = 2k/M
so,
A (k/MJ) (- k/MJ) = 2k/M
A = (k²/M²) = 2k/M
A = 2M/k
Now,
we put s = k/M J
C * k/M J ( 2k/MJ ) = 2k/M
C (2k²/m²) = 2k/M
C (k/M)
C = -M/k